Learning Community for Postgraduate Learners in the Final Year Project Course of Open University Malaysia - Hazalina Hashim (ASEAN Journal of Open and Distance Learning, 2018)
The learning community approach offers a promising way to facilitate the learning process of postgraduate learners in their final year project course at the Open University Malaysia. This is important because the final project requires a substantial amount of commitment and needs to be carried out independently. Moreover, students often experience challenges that delay or prevent them from completing their projects. Therefore, integrating a learning community into the course to address administrative or academic matters with peers and faculty members assists progression and completion. The purpose of this study was to gain insight into the learning community used by postgraduate learners for the final year project course. A survey was administered to 52 postgraduate learners and observation of the community site was conducted. The results were positive and encouraging, especially when learners tried to make sense of the learning community in order to be connected and motivated, to receive continuous support and to learn the required knowledge for the course. (Abstract by author)